2022
DOI: 10.1101/2022.09.15.508161
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neurofibromin 1 mediates sleep depth in Drosophila

Abstract: Neural regulation of sleep and metabolic homeostasis are critical in many aspects of human health. Despite extensive epidemiological evidence linking sleep dysregulation with obesity, diabetes, and metabolic syndrome, little is known about the neural and molecular basis for the integration of sleep and metabolic function. The RAS GTPase-activating gene Neurofibromin (Nf1) has been implicated in the regulation of sleep and metabolic rate, raising the possibility that it serves to integrate these processes, but … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…Moreover, both children and adults with NF1 exhibit disturbed sleep and poor sleep quality ( Licis et al, 2013 ; Johnson et al, 2005 ; Leschziner et al, 2013 ). Studies in Drosophila Nf1 mutants in mature adulthood have likewise demonstrated disruptions to both sleep and rest:activity circadian rhythms ( Williams et al, 2001 ; Bai et al, 2018 ; Bai and Sehgal, 2015 ; Brown et al, 2022 ; Machado Almeida et al, 2021 ). Specifically, adult Nf1 mutants exhibit loss of rest:activity rhythms under constant conditions, and a reduction in sleep duration with associated sleep fragmentation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, both children and adults with NF1 exhibit disturbed sleep and poor sleep quality ( Licis et al, 2013 ; Johnson et al, 2005 ; Leschziner et al, 2013 ). Studies in Drosophila Nf1 mutants in mature adulthood have likewise demonstrated disruptions to both sleep and rest:activity circadian rhythms ( Williams et al, 2001 ; Bai et al, 2018 ; Bai and Sehgal, 2015 ; Brown et al, 2022 ; Machado Almeida et al, 2021 ). Specifically, adult Nf1 mutants exhibit loss of rest:activity rhythms under constant conditions, and a reduction in sleep duration with associated sleep fragmentation.…”
Section: Introductionmentioning
confidence: 99%